2004
DOI: 10.1074/jbc.m313709200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NFκB Increases the Efficacy of Cisplatin in in Vitro and in Vivo Ovarian Cancer Models

Abstract: Whether or not inhibition of NFB increases the efficacy of cisplatin in in vitro and in vivo ovarian cancer models was investigated. We compared the basal levels of phosphorylation of IB␣ and activity of NFB between cisplatin-sensitive A2780 cells and cisplatin-resistant Caov-3 cells. The basal levels of phosphorylation of IB␣ and activity of NFB in Caov-3 cells were significantly higher than those in A2780 cells. Cisplatin caused a more marked decrease in the phosphorylation of IB␣ and activity of NFB in A278… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(100 citation statements)
references
References 48 publications
(47 reference statements)
6
90
0
4
Order By: Relevance
“…1B). At a concentration of 5 μmol/L, BAY 11-7082 had no significant inhibitory growth effects as indicated previously (5). Similarly, the DNA fragmentation assay showed that cell death induced by Taxol and parthenolide occurred via the activation of an apoptotic program (data not shown).…”
Section: Potentiation Of Taxol-induced Apoptosis By Parthenolide In Vmentioning
confidence: 58%
See 1 more Smart Citation
“…1B). At a concentration of 5 μmol/L, BAY 11-7082 had no significant inhibitory growth effects as indicated previously (5). Similarly, the DNA fragmentation assay showed that cell death induced by Taxol and parthenolide occurred via the activation of an apoptotic program (data not shown).…”
Section: Potentiation Of Taxol-induced Apoptosis By Parthenolide In Vmentioning
confidence: 58%
“…Although the molecular basis of resistance to Taxol is not well-documented, mounting evidence supports the role of intrinsically or constitutively activated nuclear factor-κB (NF-κB) in affording protection against programmed cell death. Constitutive high levels of NF-κB activity have been detected in response to chemotherapy and radiation in ovarian cancer (3)(4)(5), pancreatic cancer (6), breast cancer (7,8), and prostate cancer (9). Our recent work has revealed that nuclear RelA and cytoplasmic pI-κBα are significantly associated with a poor prognosis in cancer (10).…”
Section: Introductionmentioning
confidence: 99%
“…Ten days after transplantation, the control group received i.p. injections of DMSO whereas BAY11-7082-treated animals were injected with 5 g/g dose, three times per week for 3 weeks as described (49). Tumors were measured weekly, and volume was calculated as V (mm 3 ) ϭ A(mm) ϫ B 2 (mm 2 ) ϫ /6, B being the smaller dimension.…”
Section: Methodsmentioning
confidence: 99%
“…Cisplatin significantly inhibited cell viability in a dose-dependent manner in cisplatin-sensitive A2780 cells, but not in cisplatin-resistant A2780CP cells as reported previously. 25 After 72 h treatment, cell survival decreased from 100-68, 45 and 15% when cisplatin was administered at 1, 10 and 100 mM respectively in A2780 cells (Fig. 1A, black bars).…”
Section: Resultsmentioning
confidence: 99%